Advances in primary mitochondrial myopathies. Issue 5 (October 2019) - de Barcelos, Isabella Peixoto; Emmanuele, Valentina; Hirano, Michio
Abstract : Purpose of review: Although mitochondrial diseases impose a significant functional limitation in the lives of patients, treatment of these conditions has been limited to dietary supplements, exercise, and physical therapy. In the past few years, however, translational medicine has identified potential therapies for these patients. Recent findings: For patients with primary mitochondrial myopathies, preliminary phase I and II multicenter clinical trials of elamipretide indicate safety and suggest improvement in 6-min walk test (6MWT) performance and fatigue scales. In addition, for thymidine kinase 2-deficient (TK2d) myopathy, compassionate-use oral administration of pyrimidine deoxynucleosides have shown preliminary evidence of safety and efficacy in survival of early onset patients and motor functions relative to historical TK2d controls. Summary: The prospects of effective therapies that improve the quality of life for patients with mitochondrial myopathy underscore the necessity for definitive diagnoses natural history studies for better understanding of the diseases.